A novel electronic nose for simultaneous quantitative determination of concentrations and odor intensity analysis of benzene, toluene and ethylbenzene mixtures. Issue 96 (17th October 2015) - Jiang, Shen; Liu, Jiemin; Fang, Di; Yan, Luchun; Wu, Chuandong
<x xml:space="preserve">Abstract</x> Development of a novel E-nose system to simultaneously determine chemical concentrations and odor intensity of benzene, toluene and ethylbenzene mixtures.